Role of organic acids production in pathogenicity of Aspergillus niger inciting collar rot disease in groundnut - V.A. RASHEED; R. SARADA JAYALAKSMHI DEVI, B. BHASKAR, S. KHAYUM AHAMMED* (Indian Phytopathology, 2016)
Aspergillus niger is well known to produce organic acids such as citric acid and oxalic acid. Twelve A. niger isolates were collected from the collar rot infected groundnut plants from different growing areas of Anantapur and Chittoor districts, Andhra Pradesh, India. Highest amount of citric acid production (9.24 mg ml-1) was observed in AnA-1 isolate followed by AnC-5 (8.37 mg ml-1) and AnA-5 (8.20 mg ml-1). In case of oxalic acid production, AnA-1 isolate (7.15 mg ml-1) was significantly superior over the other isolates followed by AnA-2 (6.85 mg ml-1) and AnA-6 (6.31 mg ml-1). In vial test, oxalic acid was found to be more toxic than citric acid by exhibiting symptoms such as wilting and seedling necrosis.